A meta-analysis: the clinical value of PD-1 inhibitor or protein tyrosine kinase inhibitors in the treatment of advanced osteosarcoma - Shi, Binhao; Chang, Junli; Sun, Xingyuan; Ma, Xiaoping; Zhao, Peng; Zhou, Chujie; Wang, Yongjun; Yang, Yanping (Frontiers in Oncology, 2023)
Targeted therapies of programmed cell death protein-1 (PD-1) inhibitors and protein tyrosinase inhibitors (TKIs) have offered new treatment strategies and promoted the exploration of clinical evidence-based medicine for advanced osteosarcoma. This meta-analysis evaluated the efficacy of PD-1 inhibitors and TKIs in the treatment of advanced osteosarcoma. Trials for advanced osteosarcoma from electronic databases using keywords were comprehensively searched. Stata software was used to compare the overall survival (OS), the progression free survival (PFS), and the serious adverse events (AEs). Eight immunocheckpoint inhibitors in 327 patients from 10 clinical trials were finally evaluated. For OS, TKIs [11.67 months (95% CI, 9.32-14.01)] show more obvious advantages than PD-1 inhibitors [6.37 months (95% CI, 3.96-8.78)]. For PFS, TKIs [4.79 months (95% CI, 3.33-6.24)] are longer than PD-1 inhibitors [1.46 months (95% CI, 1.23-1.69)]. Based on the current evidences, TKIs are identified to be better than PD-1 inhibitors, and PD-1 inhibitors combined with TKIs are promising in the treatment of advanced osteosarcoma. Although there was no fatal event, attention should still be paid, especially during the combined application of PD-1 inhibitors with TKIs since their obvious AEs.